Biodiversity of Ecosystems - Hufnagel, Levente (IntechOpen, 2022)
Biodiversity of Ecosystems gives a detailed report and extensive overview of the frontiers of pure and applied biodiversity research. Chapters address such topics as abiotic factors that affect biodiversity, the efforts of conservation and sustainability, and urban and agricultural ecosystems and include case studies about special methodical problems and research approaches.